2014
DOI: 10.1186/1477-7525-12-26
|View full text |Cite
|
Sign up to set email alerts
|

Physical and psychological long-term outcome after traumatic brain injury in children and adult patients

Abstract: BackgroundSeveral studies have indicated that younger age is associated with worse recovery after pediatric traumatic brain injury (TBI) compared to elder children. In order to verify this association between long-term outcome after moderate to severe TBI and patient’s age, direct comparison between different pediatric age groups as well as an adult population was performed.MethodsThis investigation represents a retrospective cohort study at a level I trauma center including patients with moderate to severe, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 40 publications
0
32
1
Order By: Relevance
“…To analyse age-dependent treatment strategies and in-hospital outcome, the included patients were divided into six subgroups referring to Andruszkow et al [ 13 ]: Group I (“infants”): age 1–3 years. Group II (“pre-school-aged children”): age 4–6 years.…”
Section: Methodsmentioning
confidence: 99%
“…To analyse age-dependent treatment strategies and in-hospital outcome, the included patients were divided into six subgroups referring to Andruszkow et al [ 13 ]: Group I (“infants”): age 1–3 years. Group II (“pre-school-aged children”): age 4–6 years.…”
Section: Methodsmentioning
confidence: 99%
“…It is possible that the rats injured in adulthood had significant anxiety-like behavior compared to uninjured naïve rats, because the test was administered closer to their time of injury compared to rats injured in childhood (PND 17) and adolescence (PND 35). A recent retrospective clinical study reported no significant correlation between age at injury and psychological outcome parameters [49]. Few studies have evaluated the development of anxiety disorders after TBI, and further studies are necessary to understand the mechanisms of psychopathology among TBI survivors.…”
Section: Discussionmentioning
confidence: 99%
“…The validity and reliability of the questionnaire was not investigated, although some parts of it (i.e. the Barthel index) are known to be valid and reliable in cases of patients with brain injury [23].…”
Section: Participants and Proceduresmentioning
confidence: 99%